Benarkah Pendidikan Karakter Memberikan Kontribusi Terhadap Perkembangan Kemampuan Berfikir Tingkat Tinggi Siswa? - Ahmad Wahyu Hidayat; Anisa Oktaviana; Ekayanti Sulastri; Ilman Hermawan; M.Tapaul Jahidin; Edy Herianto (Jurnal Kewarganegaraan, 2024)
Abstract Character education and the development of higher-order thinking skills (HOTS) play an important role in educational transformation. This research aims to examine the contribution of character education in improving students' high-level thinking skills in the context of Pancasila and Citizenship Education (PPKn) subjects at SMPN 1 Narmada. This research uses a quantitative approach with a quasi-experimental type through a non-equivalent control group design. Data collection uses tests that meet the elements of validity, reliability, difficulty level, and distinguishability. Before testing the hypothesis statistically, the researcher ensures prerequisite tests to ensure the use of influence tests with parametric or non-parametric models. The research results show an influence of internalization of character education on students' HOTS abilities in PPKn subjects. These findings emphasize the importance of character education as a moral foundation for students in developing higher-order thinking abilities. Keywords : Character Education, Higher Level Thinking Skills, PPKn Subjects